KETERAMPILAN SOSIAL, EMPATI DAN MODERASI BERAGAMA SEBAGAI WUJUD KETERAMPILAN ABAD 21 - Asiana; Bahriani Putri, Dina; Eka Safutra, Novrian; Harto, Kasinyo; Putra Pratama, Irja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of science, technology, and globalization in the 21st century demands a shift in the educational paradigm from a focus solely on cognitive aspects toward the development of more holistic skills. This article aims to examine the role of social skills, empathy, and religious moderation as representations of 21st-century skills in education. The method used is a literature study by analyzing various relevant scientific sources. The results of the study indicate that social skills, empathy, and religious moderation are closely interconnected in shaping learners who are not only intellectually intelligent but also possess social and spiritual intelligence. Social skills help individuals interact effectively, empathy fosters care and harmonious relationships, while religious moderation instills attitudes of tolerance and balance in religious life. In conclusion, the integration of these three aspects into Islamic Religious Education is an important strategy in shaping a generation that is characterized, tolerant, and capable of facing the challenges of life in the modern era.